UJI COBA PENGGUNAAN GAS PANAS DARI TUNGKU GASIFIKASI KA YU KARET UNTUK PENGERINGAN BUI COKLAT - Tjutju Nurhayati (Jurnal Penelitian Hasil Hutan, 1994)
Hot gas of rubber wood burning on wood gasifier-combustor with capacity 3 mBTU used for cacao seed  drying at temperature ranged from 68 to 74° C. The moisture content of cacao seed prior to drying was varied from 141.93 to 7.14 %.The trial results revealed that the average of hot gas flow rate was 118.47m3/hour, rubber wood consumed  was 0.33 kg per kg dry cacao seed or 1.03 kg per wet cacao seed, with the moisture content of rubber wood ranged from 11.64 to 14.34 %. The flow rate of drying was 134.63 dry cacao seed per hour and the efficiency of hot gas conversion was 54%. The energy of hot gas consumption was 2.79 MJ per kg cacao seed and the productivity was 94. 67 KJ per kg cacao seed per hour.